Policy and legislation for a new energy paradigm : the case of the portuguese legal framework for microgeneration - Gonçalves, José (2011)
Following the European Union energy strategies and recommendations, national governments are encouraging microgeneration related investments. The national government plays an important role on the effective introduction of microgeneration technologies into the markets and daily life of citizens. In the National Plan for Action on Energy Efficiency (NPAEE), the extensive use of microgeneration technologies in a decentralized electricity system is presented as one possible system to meet the future objectives of the Portuguese government for the energy sector. Several incentives were created to promote the adoption of microgeneration technologies through policy measures such as subsidies on the electricity generated by microproducers, investment subsidies and by creating awareness/informing the public about microgeneration. This paper presents the Portuguese electricity system and the role of policy and legislation for the development of microgeneration in Portugal. The legal framework is analyzed along with the incentives and tax benefits for different microgeneration technologies. The detailed analysis of the Portuguese legal framework is made in order to ascertain the main features that may induce the project success or failure and the role of the defined payment rates namely identifying the possible success factors of these laws and regulations.